"A Bulwark Against Radicalism:" Protest Movements at the University of Pennsylvania and the Struggle for Reform, 1965‐1969. (July 2017) - Asregadoo, Ted
Abstract : This article examines faculty and student protest movements at the University of Pennsylvania (Penn) from 1965 to 1969. As the backlash against the United States' escalation of the Vietnam conflict grew on college campuses, faculty and student groups at Penn used the issue of chemical‐biological weapons research conducted at the university as a centerpiece in their protest against U.S. involvement in Vietnam. Later, students organized to protest against the expansion plans of the university into West Philadelphia neighborhoods. The administration's responses to the protest movements on campus were tolerant. And it was this outward expression of tolerance that was key in successfully containing the student and faculty's demands within a liberal‐pluralist paradigm while agreeing to minor reforms within the system.